72.3k views
4 votes
For the function f (x) = 3 (x + 7), find -1().

For the function f (x) = 3 (x + 7), find -1().-example-1
User Ameo
by
4.4k points

1 Answer

6 votes

Given:

The function is
f(x)=3(x+7)^{(1)/(4)}.

To find:

The function
f^(-1)(x).

Solution:

We have,


f(x)=3(x+7)^{(1)/(4)}

Substitute f(x)=y.


y=3(x+7)^{(1)/(4)}

Interchange x and y.


x=3(y+7)^{(1)/(4)}

Divide both sides by 3.


(x)/(3)=(y+7)^{(1)/(4)}

Taking power 4 on both sides.


\left((x)/(3)\right)^4=y+7

Subtract 7 from both sides.


\left((x)/(3)\right)^4-7=y


y=\left((x)/(3)\right)^4-7

Substitute
y=f^(-1)(x).


f^(-1)(x)=\left((x)/(3)\right)^4-7

Therefore, the correct option is C.

User Markzzz
by
5.5k points